Molecular cloning of the rat integrin alpha 1-subunit: a receptor for laminin and collagen (The Rockefeller University Press, 1990)
Integrin heterodimers mediate a variety of adhesive interactions, including neuronal attachment to and process outgrowth on laminin. We report here the cloning and primary sequence of an M-200 kD integrin alpha subunit that associates with the integrin beta 1 subunit to form a receptor for both laminin and collagen. Similarities in ligand- binding specificity, relative molecular mass and NH2-terminal sequence make this a strong candidate for the rat homologue of the alpha subunit of the human integrin VLA-1. The full-length rat alpha 1 cDNAs encode a protein containing a purative signal sequence and a mature polypeptide of 1,152 amino acids, with extracellular, transmembrane and cytoplasmic domains. Several structural features are conserved with other integrin alpha chains, including (a) a sequence motif repeated seven times in the NH2-terminal half; (b) potential Ca2+/Mg2+ binding sites in repeats 5, 6, and 7, and (c) alignment of at least 14 of 23 cysteine residues. This rat alpha 1 sequence also contains a 206-amino acid I domain, inserted between repeats 2 and 3, that is homologous to I domains found in the same position in the alpha subunits of several integrins (VLA-2, Mac-1, LFA-1, p150). The rat alpha 1 and human VLA-2 apha subunits share greater than 50% sequence identity in the seven repeats and I domain, suggesting that these sequence identities may underlie some of their similar ligand-binding specificities. However, the rat integrin alpha 1 subunit has several unique features, including a 38-residue insert between two Ca2+/Mg2+ binding domains, and a divergent 15- residue cytoplasmic sequence, that may potentially account for unique functions of this integrin.